ONLINE SHOPPING BEHAVIOUR: AN ANALYSIS WITH RESPECT TO PRODUCT CATEGORIES - DEEPA UNNITHAN AND ROHIT RAJENDRAN (ZENITH International Journal of Multidisciplinary Research, 2014)
Online shopping spree is catching up among people in India far and wide across different product categories .As the number of online shoppers are increasing day by day even in smaller cities like Cochin in Kerala,understanding their shopping behavior would help in bringing in customization rather than a one size fits all strategy irrespective of product type .In order to determine the difference in online shopping behavior with regard to different product categories, a sample size of 270 online shoppers in Kerala was contacted through mall intercepts and street surveys and data was collected .It was found that online shopping behavior of people significantly differ with different product categories. The most important factors affecting the online shopping behaviour of customers are shopping, tacit, company and website factors.Developing marketing strategies with focus on specified factors can improve the influx in online shopping in a win –win manner to both customer and retailer.